Dampak Ekspor Kelapa ke Cina terhadap Kenaikan Harga dan Ketersediaan Kelapa di Pesawaran dan Bandar Lampung - Cici Indahsari; Erlin Kurniati (SUAN PUBLISHER, 2024)
This study investigates the effects of increasing coconut exports from Indonesia to China on local price dynamics and coconut availability in two key coconut-producing areas: Pesawaran and Bandar Lampung. By employing a descriptive-qualitative approach, the research draws insights from field observations, in-depth interviews, and testimonies from coconut farmers, traders, and micro, small, and medium enterprises (MSMEs). The findings reveal a complex impact: while the rise in exports leads to higher local coconut prices—benefiting farmers by boosting their income—it also imposes economic strain on domestic consumers and small-scale industries dependent on affordable coconut supplies. The redirection of large portions of coconut harvests toward international markets has notably reduced local supply, creating scarcity and price instability in domestic trade. Moreover, the absence of effective government regulation regarding export quotas and distribution monitoring exacerbates the disconnect between international trade priorities and local consumption needs. Without intervention, this imbalance risks undermining local food security and MSME sustainability. To address these issues, the study advocates for targeted policy measures such as export control mechanisms, robust monitoring systems, and capacity-building programs for MSME actors to strengthen domestic market resilience while maintaining export competitiveness